Charterhouse Bank : banking operations undermining the law - Oji, Chijioke; Makin, Viola, 1952- ([London] : SAGE, 2016)
In June 2006, the Central Bank of Kenya (CBK) announced that it had placed Charterhouse Bank (Charterhouse) under statutory management as a result of an ongoing investigation into banking operations at Charterhouse. The CBK led the investigation into Charterhouse over allegations of money laundering and tax evasion, which involved a sum of US$1.75 billion. By October 2012, the Charterhouse controversy had still not been resolved. This book examines the investigation process.
Originally Published in: Oji, C., & Makin, V. (2013). Charterhouse Bank: Banking Operations Undermining the Law. WBS-2013-6. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Charterhouse Bank; Banks and banking -- Corrupt practices -- Case studies; Banks and banking -- Kenya -- Case studies; Business ethics -- Case studies